1997
DOI: 10.1007/s004310050581
|View full text |Cite
|
Sign up to set email alerts
|

Arginine 506 to glutamin mutation in the factor V gene in infancy and childhood: evidence of fibrinolytic impairment

Abstract: Our data indicate that hypercoagulability in children with the Arg506 to Gln mutation in the factor V gene is mainly attributed to the genetic aetiology of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…4b) were found to be significantly higher in children with APCR. 26,27 No difference was found in these studies between heterozygous infants and children without vascular occlusion and patients who previously had suffered from thromboembolism.…”
Section: Interaction Of the Factor V Leiden Mutation With Coagulationmentioning
confidence: 68%
See 2 more Smart Citations
“…4b) were found to be significantly higher in children with APCR. 26,27 No difference was found in these studies between heterozygous infants and children without vascular occlusion and patients who previously had suffered from thromboembolism.…”
Section: Interaction Of the Factor V Leiden Mutation With Coagulationmentioning
confidence: 68%
“…Few studies [26][27][28] have described the interaction between APCR and the coagulation or fibrinolytic systems in symptomatic and asymptomatic infants. The results of these studies are summarized in Figures 2 to 4.…”
Section: Interaction Of the Factor V Leiden Mutation With Coagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[144][145][146][147] Several studies have demonstrated the presence of the FV : Q506 allele in around 50% of children with venous thromboembolism. 147,148…”
Section: Epidemiology and Clinical Manifestations Of Apc Resistancementioning
confidence: 99%
“…TM corrected the premature lysis of clots prepared from factor X, IX, VIII and XI deficient plasmas in vitro (24) and TAFI dependent down regulation of fibrinolysis was shown to be augmented by both soluble (15,25,26) and cellular (27) TM. Modulation of fibrinolysis by APC has been de-scribed both in vitro (19,20,22,28) and in vivo (29)(30)(31) whereas factor V Leiden , in which the inactivation of factor Va by APC is severely compromised due to a mutation in factor V (Arg 506 ǞGln), was shown to enhance the down regulation of fibrinolysis (32,33).…”
Section: Introductionmentioning
confidence: 99%